2010
DOI: 10.1103/physrevb.81.214115
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic structural distortion and superexchange interaction in the orthorhombic rare-earth perovskitesRCrO3

Abstract: High-resolution neutron powder diffraction has been applied to determine the structural evolution in the orthorhombic perovskite RCrO 3 family. The structural distortions observed have been found to be closely related to the dramatic variation in the magnetic ordering temperature T N . In addition to the reduction in the orbital overlap integral that can account for the change in T N in the RFeO 3 family, the effect of t-e hybridization due to the structural distortions are responsible for the dramatic change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 20 publications
7
83
1
Order By: Relevance
“…1). This is in contrast with LaCrO 3 and other orthochromites with relatively large Ln, in which the octahedra are nearly regular [17]. The electronic configuration of the Cr 3+ ions is not degenerate and the uniaxial elongation of the octahedra in the ACrO 3 perovskites studied here is thus a secondary structural effect due to the large octahedral tilting rather than due to Jahn-Teller instability.…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…1). This is in contrast with LaCrO 3 and other orthochromites with relatively large Ln, in which the octahedra are nearly regular [17]. The electronic configuration of the Cr 3+ ions is not degenerate and the uniaxial elongation of the octahedra in the ACrO 3 perovskites studied here is thus a secondary structural effect due to the large octahedral tilting rather than due to Jahn-Teller instability.…”
Section: Resultscontrasting
confidence: 63%
“…It was also noted that with a decrease of the radius of the Ln cation, the magnetic ordering temperature was monotonically reduced. Zhou et al have discussed the relationship between structural distortions and AFM magnetic transition temperature [17]. Their work highlights the important role of t 2g − e g hybridization, in addition to the reduction of the orbital overlap integrals.…”
Section: Introductionmentioning
confidence: 99%
“…-O bond distance of 2.0 Å in RCrO 3 (16). It is also worthwhile to note that the distance from Pb atoms to O atoms (connected to Cr 3+ atoms) is 2.43−2.56 Å, which is substantially shorter than the 2.85 Å estimated for the ideal cubic case; the shorter Pb-O bonds are indicative of a possible contribution of the Pb-O interaction to stabilizing the CD phase (vide infra).…”
Section: +mentioning
confidence: 99%
“…indicates that the change in T N Cr induced by the change in R-ion radii (chemical pressure), [21,35] and in the case of external pressure, compressions at Cr-O plays a dominating role over octahedral tilts in pressure dependent change in T N Cr .…”
Section: -2497xmentioning
confidence: 99%
“…However, there were no studies reported on the role of R-ion radii in the pressure dependent orthorhombic distortion despite its obvious relation with the degree of octahedral tilts. [18] Furthermore, Cr 3+ -O-Cr 3+ exchange interactions are sensitive to the octahedral tilt angles [21] and thereby play a crucial role in the pressure induced changes in the magnetic transition temperature (T N Cr ), which would regulate the magnetic properties of these materials.…”
mentioning
confidence: 99%